General Government Balance Shocks and Their Impact on Some Tunisian Macroeconomics Variables: Evidence from a VAR Model - Bouazizi, Tarek; Hadhek, Zouhaier; Lassoued, Mongi (International Journal of Economics and Financial Issues, 2020)
This paper reinterprets the mixed evidence of the relationship and the long-run relationships between the general government budget (GGB) and some macroeconomics variables (current account deficit, fixed investment (FI), gross savings (GS), government consumption (GC) and gross domestic product (GDP) and GDP per capita) in Tunisia using the VAR model. The period of the study runs from 1975 until 2018 with a yearly data. We obtain evidence of fluctuations in current account deficit (CAD) as a response to GGB shocks. But during the end of the period, the shocks of the CAD have a negative effect on the GGB and the two deficits are found to be positively linked. Our results suggest that impulse responses of budget deficit did a weak impact on gross saving of Tunisia, but the one savings strategy has a positive effect on this deficit. On the basis of results published in the empirical literature, the general government deficit increase the fixed investment, but the response of the GGB to FI shocks is weak and almost stable. In addition, fiscal deficit shocks have a positive effect on consumption. Any increase in the GGB to an increase in consumption. GDP per capital’s impulse responses to GGB shocks is characterized by such stable and positive effects. The Granger causality test indicates that causation run from GGB shocks to most macroeconomics variables with the exception of the CAD, implying that variation in general government deficit is explained by increasing public spending and also by these five other variables. Keywords: VAR modeling, Budget Deficit, Macroeconomics JEL Classifications: C22, E21, H62 DOI: https://doi.org/10.32479/ijefi.10372